Peningkatan Produktivitas dan Pendapatan Masyarakat melalui Diversifikasi Usaha Tani Pembuatan Pupuk Organik - Sulastri, Sulastri; Adam, Mohamad; Saftiana, Yulia; Nailis, Welly; Putri, Yulia Hamdaini (Penerbit Goodwood, 2023)
Purpose: The purpose of this service activity is to provide assistance in diversifying the business of farming communities in the village to provide guidance and training on business diversification. Method: The method is in the form of training and mentoring. The participants were 30 farmers from Pagar Dewa village, Jarai Lahat district. Results: The activity was carried out well because the level of understanding of the farming community who participated in the training was high. Conclusion: Farming diversification in the form of making organic fertilizers can be an alternative business that is still related to the competitive value farming value chain. This fertilizer can also be used alone to reduce the operational costs of farming which tend to be high but the price of marketed vegetable products is relatively cheap. Limitations: This service activity is limited to only one location in the Lahat district. Contribution: This activity is useful for improving household economic welfare.